Application of Classical Music Therapy to Reduce the Level of Auditory Hallucinations in Patients with Psychiatric Disorders at Dr. RM Soedjarwadi Regional Mental Hospital - Sholihah, Amalia Radhiyah; Gati, Norman Wijaya; Reknoningsih, Wahyu (Al-Hijrah Indonesia, 2025)
Background: Hallucinations are perceptual disturbances that occur without external stimuli, affecting one or more of the five senses while the individual is fully conscious. In 2024, schizophrenia patients experiencing hallucinations accounted for 2,335 (54.2%) of total admissions at Dr. RM Soedjarwadi Regional Mental Hospital, Central Java Province, making them the largest patient group treated at the facility. Non-pharmacological interventions play a vital role in managing psychiatric symptoms, and music therapy, particularly classical music has shown potential in reducing psychological distress and improving cognitive and emotional functioning. Objective: This study aims to evaluate the effectiveness of classical music therapy in reducing the severity of auditory hallucinations among patients with psychiatric disorders at Dr. RM Soedjarwadi Regional Mental Hospital. Methods: A descriptive case study design was employed, with two respondents undergoing classical music therapy based on the pretest-posttest method. The Auditory Hallucinations Rating Scale (AHRS) questionnaire was used to assess changes in the frequency, intensity, and impact of hallucinations before and after the intervention. Results: Prior to the intervention, both respondents exhibited severe levels of auditory hallucinations, with baseline AHRS scores of 23 and 26, respectively. Following the implementation of classical music therapy, scores decreased significantly to 8 and 9, both falling within the mild category. Conclusion: The findings indicate that classical music therapy, particularly the use of Mozart compositions, is effective in reducing the severity of auditory hallucinations in patients with psychiatric disorders. This suggests that music therapy can serve as a valuable non-pharmacological adjunct in the management of hallucinatory symptoms in clinical psychiatric settings.